Copaifera duckei oleoresin as a novel alternative for treatment of monogenean infections in pacu Piaractus mesopotamicus - da Costa, Jaqueline Custódio [UNESP]; Valladão, Gustavo Moraes Ramos [UNESP]; Pala, Gabriela [UNESP]; Gallani, Sílvia Umeda [UNESP]; Kotzent, Suzana [UNESP]; Crotti, Antônio Eduardo Miller; Fracarolli, Letícia; da Silva, Jonas Joaquim Mangabeira; Pilarski, Fabiana [UNESP] (Elsevier, 2017)
Monogeneans are major parasites of fish and cause large economic losses in aquaculture. Treatment for this parasitic infection is done with products that are mostly toxic to fish and the environment. Essential oils (EOs) of Melaleuca alternifolia and Mentha piperita and the oleoresin (OR) of Copaifera duckei were tested for their in vitro anthelmintic activity against the monogenean parasites (Anacanthorus penilabiatus and Mymarothecium viatorum) of pacu Piaractus mesopotamicus. Naturally infected gills were bathed with the herbal solutions (100, 200, 400, 800, and 1600 mg/L) and monitored every 15 min for 4 h. Because of its greater efficacy in vitro (p < 0.05) compared to the other herbal medicines, C. duckei OR was selected for in vivo testing. The in vivo treatment consisted of 10 and 50 mg/L baths of C. duckei OR for 10 min. Parasitological, hematological, and histological analyses were conducted post-bath and seven days after treatment. Parasite loads decreased by approximately 45% in fish treated with 50 mg/L of C. duckei OR. No hematological changes caused by treatment with C. duckei OR at 10 and 50 mg/L were observed. Histology revealed branchial and hepatic alterations in fish from all groups, whereas spleen and kidney tissues were not affected. Histopathological alterations observed in all fish were due to parasitism or nutritional/farming conditions. Hematological and histological results showed that short baths were safe for fish. Based on the strong anthelmintic activity observed, C. duckei OR offers a promising alternative treatment against monogenean parasites.
Keywords: Aquaculture; Chemotherapeutics; Herbal medicine; Natural treatment; Parasite; Phytotherapy